Struktur Komunitas Zooplankton Di Danau Hanjalutung Berdasarkan Jenis Tutupan Vegetasi - Tania Serezova Augusta (Fakultas Peternakan Universitas Kristen Palangka Raya, 2013)
This research was aimed to analyze the structure of zooplankton community; also to show the relationship of water quality in Hanjalutung Lake based on kinds of vegetation cover. The benefits of this research was it to provide information and recommendation in utilizing of Hanjalutung as business place of fishery cultivation. This research was conducted at waters of Hanjalutung Lake, District of Petuk Katimpun, Palangka Raya, Central Kalimantan Province. This study was performed from February 2013 in rainy season (high water season) until August 2013 and dry season (low water season). The result of this research showed that water quality parameters were still in the range that can be tolerated by zooplankton. Zooplankton community in Hanjalutung Lake were dominated by small zooplankton of Rotifera Phylum. Most zooplankton were caught at zone IV, from Rotifera Phylum of Trichocerca. Overall the dynamics of zooplankton were significantly affected by water transparancy and pH.